2014
DOI: 10.1038/nm.3442
|View full text |Cite
|
Sign up to set email alerts
|

Fas ligand–mediated immune surveillance by T cells is essential for the control of spontaneous B cell lymphomas

Abstract: Loss of function of the tumor suppressor gene PRDM1 (also known as BLIMP1) or deregulated expression of the oncogene BCL6 occurs in a large proportion of diffuse large B cell lymphoma (DLBCL) cases. However, targeted mutation of either gene in mice leads to only slow and infrequent development of malignant lymphoma, and despite frequent mutation of BCL6 in activated B cells of healthy individuals, lymphoma development is rare. Here we show that T cells prevent the development of overt lymphoma in mice caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 76 publications
6
80
0
Order By: Relevance
“…In fact, it was recently shown that Tc cells use FasL to eradicate transplanted B-cell lymphoma cells in RAG1 (recombination activating gene 1)-deficient mice (47). This result confirms previous findings using animals with natural mutations in Fas (lpr) or FasL (gld; refs.…”
Section: Cancer Immunosurveillancesupporting
confidence: 90%
“…In fact, it was recently shown that Tc cells use FasL to eradicate transplanted B-cell lymphoma cells in RAG1 (recombination activating gene 1)-deficient mice (47). This result confirms previous findings using animals with natural mutations in Fas (lpr) or FasL (gld; refs.…”
Section: Cancer Immunosurveillancesupporting
confidence: 90%
“…T cells play an important role in suppressing spontaneous B-cell lymphoma (36) and are prominent features of the FL microenvironment. We found that T cells that were infiltrating CREBBP mutant FL tumors showed transcriptional signatures of decreased T-cell proliferation, suggesting the CREBBP mutation-associated decreases in MHC class II result in lower levels of T-cell stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been proposed that FasL-driven CD8 C T cell killing could be essential for the elimination of large and/or disseminated tumors. [33][34][35] However, it should be noted that tumors can lose Fas expression or develop mutations in the cell death pathway engaged by FasL, thus developing resistance to FasL/Fas-mediated CD8 C T cell cytotoxicity. Other mechanisms by which tumors can resist CD8 C T cell cytotoxicity are increased expression of anti-apoptotic molecules such as Bcl -2, Bcl -xl, and Mcl -1 and changes in components of the cytoskeleton that impair the formation of stable immunological synapses between cytotoxic CD8…”
Section: Cd8mentioning
confidence: 99%